2016
DOI: 10.1002/jbm.b.33761
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and physical properties of glass‐fiber‐reinforced thermoplastics for non‐metal‐clasp dentures

Abstract: Recently, non-metal-clasp dentures (NMCDs) made from thermoplastic resins such as polyamide, polyester, polycarbonate, and polypropylene have been used as removable partial dentures (RPDs). However, the use of such RPDs can seriously affect various tissues because of their low rigidity. In this study, we fabricated high-rigidity glass-fiber-reinforced thermoplastics (GFRTPs) for use in RPDs, and examined their physical properties such as apparent density, dynamic hardness, and flexural properties. GFRTPs made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In accordance with the present study, Movade et al 4 found that 2% PPF group of specimens exhibited improved flexural strength values and they also presented that PPF groups of specimens had higher toughness values than glass fiber and polyethylene fiber groups of specimens. Similarly, Nagakura et al 16 suggested that glass fiber and PPF reinforcements have beneficial effect on the physical properties of denture base resin.…”
Section: Discussionmentioning
confidence: 95%
“…In accordance with the present study, Movade et al 4 found that 2% PPF group of specimens exhibited improved flexural strength values and they also presented that PPF groups of specimens had higher toughness values than glass fiber and polyethylene fiber groups of specimens. Similarly, Nagakura et al 16 suggested that glass fiber and PPF reinforcements have beneficial effect on the physical properties of denture base resin.…”
Section: Discussionmentioning
confidence: 95%
“…RPDs with resin clasps have superior esthetic performance to metal clasps and high elasticity to allow the same degree of retentive force as metal clasps (1)(2)(3)(4). RPDs with resin clasps are fabricated with thermoplastic denture base resin, the bending properties of which influence the retentive force, fitness, and transmission of stress to the abutment teeth (5)(6)(7)(8). For retentive force, past studies show that 5-10 N per tooth is required for the retention device of an RPD with wire clasps (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The content of >50% of fibers in the mass base significantly influences the above-mentioned characteristics. 22 The presence of <10% of fibers in the denture composition does not change the physical properties. However, besides glass fibers content, their diameter is very important as well.…”
mentioning
confidence: 99%
“…1,4,10,17,20 Some disadvantages of thermoplastic materials may be reduced by the introduction of glass fibers. 22 Glass fibers increase the strength of elastic materials, improve their bending strength and resistance to congelation. The content of >50% of fibers in the mass base significantly influences the above-mentioned characteristics.…”
mentioning
confidence: 99%
See 1 more Smart Citation